A Central Symmetrical and Low-Profile Omnidirectional Circularly Polarized Antenna. (24th September 2019) - Wu, Zhe; Yang, Lin; Wu, Jiaji; Wu, Zhensen; Li, Xi; Yun, Yu
Abstract : In this paper, a compact circularly polarized (CP) antenna with omnidirectional radiation is presented, which has a central symmetric configuration (CSC) and planar structure. It consists of three identical end-fire CP antenna units. Based on the combination of two parallel complementary current sources, each unit cell can be realized by a scalloped cavity and a couple of curved strip lines. Due to a single-layer circular structure with low profile, this configuration can be excited by a coaxial probe in the centre of the whole frame simultaneously. In addition, this prototype was miniaturized with a diameter of 32 mm (0.266λ r, the wavelength of the centre frequency in free space is represented by  λ r ) and a height of 1.5 mm (0.012λ r ). Centre resonance frequency 2.492 GHz is selected, resulting in an omnidirectional radiation and impedance bandwidth (VSWR ≤ 2) of 25 MHz (2481–2506 MHz).